RISKY BEHAVIOUR AMONG ROAD USERS AT LOCATIONS WITH HIGH PROBABILITY OF CRASH OCCURRENCE - Santiago CARDONA URREA; Diego Alexander ESCOBAR; Carlos Alberto MONCADA (Geo Journal of Tourism and Geosites)
The aim of this research is (1) to identify places with a high probability of crash occurrence (LHPCO) in Villavicencio-Colombia and (2) to carry out road safety audits in each LHPCO to evaluate the behaviour of road users and speed measurements. As a methodological structure, the analysis of crash data is considered, linked to assessments of road safety audits, with which it is obtained that motorcyclists are overrepresented in the statistics of road injuries. In addition, a total of seven LHPCOs were identified. In these locations, pedestrians engaged in a large number of risky behaviours, and speed measurements indicated that car drivers select high speeds near crosswalks. Interventions such as public education or police enforcement are needed to reduce the risky behaviour of pedestrians and motorists near high-risk locations.